Pneumonia due to antibiotic resistant Streptococcus pneumoniae and Pseudomonas aeruginosa in the HAART era. Issue 938 (5th January 2004) - Allen, S H; Brennan-Benson, P; Nelson, M; Asboe, D; Bower, M; Azadian, B; Gazzard, B; Stebbing, J
Abstract : Antibiotic resistance profiles are useful in directing therapeutic strategies during bacterial infections. Patterns of antimicrobial resistance in Streptococcus pneumoniae and Pseudomonas aeruginosa associated pneumonia were investigated in an HIV-1 infected cohort during the era of highly active antiretroviral therapy. The median CD4 count at presentation was significantly lower for cases of P aeruginosa than for S pneumoniae . However, the number of antibiotic resistant cases of P aeruginosa decreased throughout the study period, while the incidence of S pneumoniae remained unchanged. In contrast to pneumococcal pneumonia, we show that antiretrovirals have protected from pneumonia due to antibiotic resistant P aeruginosa . These findings have implications for the treatment of individuals presenting with serious infections in which antibiotic therapy needs to be instituted before identification and sensitivities are known.